Pride in my past: Influencing sustainable choices through behavioral recall. Issue 4 (27th January 2019) - Rowe, Zoe O.; Wilson, Hugh N.; Dimitriu, Radu; Charnley, Fiona J.; Lastrucci, Giovanna
Abstract: Emotional appraisal research has demonstrated that recalling a past behavior and its associated emotions can influence future behavior. However, how such recalled emotions shape sustainable consumer choice has not been examined. This study examines the role of recalled pride and guilt in shaping sustainable purchase intentions and the mediating role of anticipated pride and guilt. A conceptual model is proposed for motivating sustainable purchase intentions through the emotions associated with the behavioral recall. The model is applied in two experiments with online consumers examining purchase intentions of low carbon cars. Recalling feelings of pride associated with a past sustainability‐related behavior increases sustainable purchase intention, as compared with a neutral recall. This effect occurs through the mediation of both anticipated pride at the prospect of a sustainable behavior choice and anticipated guilt if the future choice is not sustainable. Similar hypotheses relating to recalled guilt at past unsustainable behavior were not supported. The study contributes to research on sustainable consumption, revealing an emotional route by which past behavior can influence future behavior. It also adds to emotional appraisal research by showing the role of specific self‐conscious emotions in forming this route, as prior research has focused more broadly on emotional valence.